2020
DOI: 10.1038/s42003-020-01517-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular condensates as arbiters of biochemical reactions inside the nucleus

Abstract: Liquid-liquid phase separation (LLPS) has emerged as a central player in the assembly of membraneless compartments termed biomolecular condensates. These compartments are dynamic structures that can condense or dissolve under specific conditions to regulate molecular functions. Such properties allow biomolecular condensates to rapidly respond to changing endogenous or environmental conditions. Here, we review emerging roles for LLPS within the nuclear space, with a specific emphasis on genome organization, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 98 publications
1
59
0
Order By: Relevance
“…Recently, biomolecular condensates between proteins and nucleic acids formed via LLPS have been proposed to be associated not only with the regulation of gene transcription ( Hnisz et al, 2017 ), DNA replication ( Parker et al, 2019 ), and DNA damage repair ( Laflamme and Mekhail, 2020 ), but also with the organization of specific chromatin domains ( Erdel and Rippe, 2018 ; Larson and Narlikar, 2018 ; Gibson et al, 2019 ). Although the major factor in the formation of these condensates is the LLPS-prone proteins, the DNA itself is also critical in this event.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biomolecular condensates between proteins and nucleic acids formed via LLPS have been proposed to be associated not only with the regulation of gene transcription ( Hnisz et al, 2017 ), DNA replication ( Parker et al, 2019 ), and DNA damage repair ( Laflamme and Mekhail, 2020 ), but also with the organization of specific chromatin domains ( Erdel and Rippe, 2018 ; Larson and Narlikar, 2018 ; Gibson et al, 2019 ). Although the major factor in the formation of these condensates is the LLPS-prone proteins, the DNA itself is also critical in this event.…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular condensates represent a class of dynamic membrane-less bodies that are central in compartmentalizing subcellular biochemical processes in viruses 1 , bacteria 2,3 , yeast 4,5 , and human 6 . Past studies have reported a variety of biomolecular condensates with a broad range of physiological functions including stress response 7,8 , mRNA processing 9 , transcriptional activity control [10][11][12] , and genome organization 13 .…”
mentioning
confidence: 99%
“…However, the role of LLPS in A compartment organization is currently an active area of research. Histone acetylation disrupted compacted chromatin droplets, and multi-bromodomain proteins, such as BRD4, induced LLPS of acetylated histones, forming liquid droplets (30,31). Growing evidence suggests that phase separation is one of the critical mechanisms of chromatin compartmentalization in 3D genome organization, although further efforts are needed to decipher the dynamics and mechanisms of regulation involving phase separation in chromosome compartmentalization.…”
Section: Chromosome Territories and A/b Compartmentsmentioning
confidence: 99%